Positive Deviance Status Gizi Balita pada Keluarga Miskin di Desa Oeltua Wilayah Kerja Puskesmas Baumata Kabupaten Kupang - Karolina T. Bokilia; Utma Aspatria; Sarci M. Toy (Universitas Nusa Cendana, 2021)
Stunting commonly occurs on susceptible groups such as indigent families. However, there are cases where nourished babies are also found in those families despite having financial problems. This type of case is called a positive deviance found among people who are living in poverty. The research aims to explore conditions of indigent families in Oeltua Village with nourished babies. The research was qualitative using a study case approach with the subjects were poor families without stunted children in Oeltua village. The subject were selected based on the purposive sampling technique by applying the case criteria. Instruments used in this research were questionnaires, voice recorders and documentations. Data analysis was conducted by qualitative analysis based on the obtained data from in-depth interviews on the informants. The result showed that the feeding pattern, personal hygiene and given health services for the babies were shown sufficiently good. Families managed to provide good nutritions by buying foods within the household budget and harvesting vegetables from the home garden. In addition, the families maintained good personal hygiene and accessed health services to improve babies nutritional status. The support from health workers were essential in monitoring babies` nutritional status, advising mothers on nutrition and handling malnutrition. The positive deviance behavior needs to be addressed onto families by empowering and sharing among families assisted by public health office and local clinics to improve health status.